2021
DOI: 10.4103/sjg.sjg_332_20
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to research productivity among gastroenterologists and hepatologists in Saudi Arabia

Abstract: Background: Clinical research is essential for the advancement of medical knowledge and evidence-based medical practice. In this study, we aimed to identify barriers that limit research productivity among gastroenterologists in Saudi Arabia. Methods: We conducted a national online survey targeting gastroenterologists in Saudi Arabia. Participants were asked about the patterns of their practice, their prior research activities, and potential barriers to research producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Followed by a lack of funding and compensation with (77.6%) and lack of a statistician (68.2%). Additionally, Improvement of personal C.V and enhancement of research skills are the two most reported goals, 81.1% and 80%, respectively [17]. (Soubhanneyaz) Conducted a cross-sectional study among 132 family medicine residents in the Joint Program of Family Medicine Post-Graduate Studies, Medina, Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Followed by a lack of funding and compensation with (77.6%) and lack of a statistician (68.2%). Additionally, Improvement of personal C.V and enhancement of research skills are the two most reported goals, 81.1% and 80%, respectively [17]. (Soubhanneyaz) Conducted a cross-sectional study among 132 family medicine residents in the Joint Program of Family Medicine Post-Graduate Studies, Medina, Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…Evidences suggest that postgraduate medical trainees who participate in adequate research activities have better critical thinking skills, medical supervision, and lifelong learning [3,4]. Since replacing the individualized, unsystematic decisions in clinical practice in 1992, evidence-based medicine has been the accepted approach to patient care.5 Clinical research is the foundation of evidence-based medicine and a key to providing the best possible care for patients [6][7][8]. Research activities have been improving recently in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigators performed multivariate analysis to examine associations between diverse factors and research productivity. It was concluded that the top barrier to research is insufficient time [23]. Both Institutional factors and Individual factors seem to play a role in research productivity.…”
Section: Time Constraint For Researchmentioning
confidence: 99%